The effect of a single‐sided pole shoe and slot on reducing torque ripple in a switched reluctance motor. (6th May 2020) - Ma, Hongzhong; Huang, Chaozhi; Liu, Xiping; Shi, Wangfeng; Liu, Wei
Summary: The switched reluctance motor (SRM) has the high level of vibration and noise, whose application is greatly limited in many fields. In this article, a novel stator for a SRM is designed to reduce torque ripple and is suitable for one‐directional or low‐speed reverse rotation. On the one hand, a shoe is added to the stator pole side in the rotating forward direction from the completely unaligned to the aligned position. On the other hand, a slot is set on the top of stator tooth. First, causes of vibration and torque ripple are analyzed. Second, it is indicated by the equivalent magnetic circuit (EMC) method that the air gap permeability of the model with the single‐sided pole shoe is larger than that of the conventional model in the nonoverlapping region between the stator and rotor. The influences of the angle and height of shoe on the air gap magnetic density, radial force, and torque ripple are analyzed. Third, the results from EMC method show that the radial force can be reduced by opening a slot at the top of stator pole arc. The width and depth of slot which has effect on the radial force and torque ripple are analyzed. Finally, finite element analysis results show that the decreases of 34.52% for the radial force wave peak and 43.39% for the torque ripple are achieved at the cost of a decrease of 8.54% for the average torque of the single‐sided pole and the slot model of the stator pole compared with the conventional model. Some experiments for the two prototypes verify that the torque ripple and radial force can be reduced by adopting the new model.